In Situ Cold Perfusion of the Liver on Cardiopulmonary Bypass: Coagulopathy and Its Correction. Issue 10 (15th November 2018) - Haque, Mohammed; Van Rensburg, Adriaan; McCluskey, Stuart; Meineri, Massimiliano; Parotto, Matteo
Abstract : We report a case of profound coagulopathy after the dual insult of cold in-situ perfusion of the liver and cardiopulmonary bypass in a patient undergoing complex hepatobiliary and cardiovascular surgery. Management of this coagulopathy with conventional blood products was hindered by elevated venous pressures, thought to contribute to persistent bleeding and risked liver and right ventricular dysfunction, necessitating a change in strategy. Anesthesiologists should consider fluid-restrictive strategies to correct coagulopathy in combined liver and cardiac surgery.